Pengembangan Aplikasi Login Menggunakan Pengenalan Wajah Dan Kedipan Mata - Frindi Mangimbulude; Pinrolinvic D.K. Manembu; Feisy Diane Kambey (CogITo Smart Journal, 2023)
Facial recognition technology is widely used as one of the technologies to authenticate someone. However, some devices do not yet have a facial recognition component that is able to recognize real people who have been recognized or only photos because they only embed a 2D facial recognition system which is less secure, especially on devices with low specifications and older devices, and there are still many people at this time who still use such devices but they also need security. So in this study a login system with facial recognition and eye blink detection was created which aims to provide more security on older devices or devices with low specifications. This study uses the Local Binary Pattern Histogram facial recognition algorithm and the Face landmark wink detection algorithm from the dlib library. So that the application can run properly on older devices or devices with low specifications.